2021
DOI: 10.3390/microorganisms9030617
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Functional Characteristics of the Gill and Gastrointestinal Microbiota and Its Correlation with Intestinal Metabolites in NEW GIFT Strain of Farmed Adult Nile Tilapia (Oreochromis niloticus)

Abstract: The gill and gastrointestinal tract are primary entry routes for pathogens. The symbiotic microbiota are essential to the health, nutrition and disease of fish. Though the intestinal microbiota of Nile tilapia (Oreochromis niloticus) has been extensively studied, information on the mucosa-associated microbiota of this species, especially the gill and gastrointestinal mucosa-associated microbiota, is lacking. This study aimed to characterize the gill and gastrointestinal mucosa- and digesta-associated microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 88 publications
5
31
0
Order By: Relevance
“…The pond water had the lowest abundance of Proteobacteria , whereas it was highly enriched in the mullet gill. The dominance of Proteobacteria in the external microbiome of teleost fish has been indicated in previous studies ( Chiarello et al, 2015 ; Legrand et al, 2018 ; Zhang et al, 2019 ; Wu et al, 2021 ). Communities with enriched Proteobacteria may reflect the advantage of unique niche colonization for enhancing microbial growth ( Zhang et al, 2019 ) and a significant role in the microbiome mucosal barrier for this bacterial phyla.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The pond water had the lowest abundance of Proteobacteria , whereas it was highly enriched in the mullet gill. The dominance of Proteobacteria in the external microbiome of teleost fish has been indicated in previous studies ( Chiarello et al, 2015 ; Legrand et al, 2018 ; Zhang et al, 2019 ; Wu et al, 2021 ). Communities with enriched Proteobacteria may reflect the advantage of unique niche colonization for enhancing microbial growth ( Zhang et al, 2019 ) and a significant role in the microbiome mucosal barrier for this bacterial phyla.…”
Section: Discussionsupporting
confidence: 67%
“…Communities with enriched Proteobacteria may reflect the advantage of unique niche colonization for enhancing microbial growth ( Zhang et al, 2019 ) and a significant role in the microbiome mucosal barrier for this bacterial phyla. Interestingly, several opportunistic aquatic pathogens, such as Aeromonas , Vibrio , and Plesiomonas , belong to Proteobacteria ; and their presence may stimulate and maintain mucosal immunity ( Wu et al, 2021 ). The higher abundance of Proteobacteria in external microbial communities was followed by Fusobacteriota and Firmicutes , which have been reported as ubiquitous phyla in the external microbiome of the fish ( Reverter et al, 2017 ; Zhang et al, 2019 ; Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species in Mycobacterium have been reported to enhance the immunity in aquatic species like salmonids without any negative effects (Prathiviraj et al, 2021). However, several studies indicated that Mycobacterium might be a potential opportunistic pathogen to cause chronic long-term persistent infections in the gut of zebra fish (Wang et al, 2021;Wu et al, 2021). In our study, the relative The Israeli Journal of Aquaculture -Bamidgeh • IJA.73.2021.1520998 abundance of Mycobacterium was higher in CAs group, while no intestine health problem was observed during the cultivation process.…”
Section: Discussionmentioning
confidence: 41%
“…Indeed, seafood has been characterized as an ideal reservoir of pathogenic microbes that are closely related to human diseases (e.g., via the production of neurotoxin), such as some species belonging to the genus Clostridium e.g., C. botulinum , C. perfringens [ 40 , 41 ], the presence of which, is mainly linked with a potential sewage contamination [ 42 ]. Furthermore, Ralstonia was found to dominate in the gut of cultured sea bass, Nile Tilapia and Maryland blue crab [ 43 , 44 , 45 ]. This bacterial group may be responsible for an initial deterioration of sensory attributes, via the production of specific enzymes, closely linked to food/seafood spoilage, such as lipase [ 46 ].…”
Section: Discussionmentioning
confidence: 99%